2022
DOI: 10.1113/jp282894
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced modulation of neuroinflammation in ageing

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…It is possible that exercise also reduces gliosis and glial proliferation [103]. Moreover, via its action on CNS glial cells, regular aerobic exercise has been shown to provide an adaptive advantage against perturbations to homeostasis, such as immunological challenge or ageing in animal models [174]. A systematic review and meta-analysis involving 13 RCTs and 514 participants, revealed that physical activity had positive effects on decreasing TNF-α and CRP (pro-inflammatory), while significantly improving BDNF and IGF-1 (neuroprotective) [175].…”
Section: Specifically Targeting Neuroinflammation To Improve Sleep An...mentioning
confidence: 99%
“…It is possible that exercise also reduces gliosis and glial proliferation [103]. Moreover, via its action on CNS glial cells, regular aerobic exercise has been shown to provide an adaptive advantage against perturbations to homeostasis, such as immunological challenge or ageing in animal models [174]. A systematic review and meta-analysis involving 13 RCTs and 514 participants, revealed that physical activity had positive effects on decreasing TNF-α and CRP (pro-inflammatory), while significantly improving BDNF and IGF-1 (neuroprotective) [175].…”
Section: Specifically Targeting Neuroinflammation To Improve Sleep An...mentioning
confidence: 99%
“…Exercise has also been shown to enhance expression of neurotrophins, such as brain derived neurotrophic factor (BDNF), that regulate neurogenesis, neuronal function and survival ( 27 ). Finally, exercise may also modulate glia cell phenotype and function ( 28 ).…”
Section: Exercise Intervention Studies Are Conducted Late In People W...mentioning
confidence: 99%
“…In the paper 'Exercise-induced modulation of neuroinflammation in ageing' , Barad, Augusto and Kelly discuss age-related disequilibrium within the central nervous system (CNS) and the critical role that inter-organ communication may play in CNS dysfunction, particularly highlighting the role of immune cells (Barad et al, 2023). They assess the evidence showing that endurance exercise can induce adaptive benefits to neuroimmune communications that can help ameliorate homeostatic challenges caused by immunological stresses or ageing.…”
mentioning
confidence: 99%